Experience in a Climate Simulator: Influence of Probability Function and Feedback on Decisions Against Climate Change - Choudhary, Gitanshu; Dutt, Varun (Frontiers in Psychology, 2021)
Research indicates that people continue to exhibit “wait-and-see” preferences towards climate change, despite constant attempts to raise awareness about its cataclysmic effects. Experiencing climatic catastrophes via simulation tools have been found to affect people's perception of climate change and promote pro-environmental behaviors. However, not much is known about how experiential feedback and probability of climate change in a simulation influences people’s decision. We developed a web-based tool called Interactive Climate Change Simulator (ICCS) to study the impact of different probabilities of climate change and the availability of feedback on the monetary actions (adaptation or mitigation) taken by individuals. A total of 160 participants from India voluntarily played ICCS across four between-subject conditions (N= 40 in each condition). The conditions differed based on the probability of climate change (low or high) and availability of feedback (absent or present). Participants made mitigation and adaptation decisions in ICCS over multiple years and faced monetary consequences of their decisions. There was a significant increase in mitigation actions against climate change when the feedback was present compared to when it was absent. The mitigation and adaptation investments against climate change were not significantly affected by the probability of climate change. The interaction between probability of climate consequences and availability of feedback was significant: In the presence of feedback, the high probability of climate change resulted in higher mitigation and adaptation investments against climate change. Overall, the experience gained in the ICCS tool helped alleviate peoples 'wait-and-see' preferences and increased the monetary investments to counter climate change. Simulation tools like ICCS have the potential to increase peoples' understanding of climatic disasters and can act as a useful aid for educationalists and policymakers.